2017
DOI: 10.1155/2017/2035851
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Percutaneous Nephrolithotomy versus Retrograde Intrarenal Surgery for Upper Urinary Stones: A Systematic Review and Meta-Analysis

Abstract: Minimally invasive percutaneous nephrolithotomy (mini-PCNL) and retrograde intrarenal surgery (RIRS) are both alternatives for PCNL to treat renal calculi. This study is aimed at comparing the stone-free rate (SFR) and other surgery parameters of two approaches for treating upper urinary calculi. We performed this meta-analysis in September 2016 by searching studies about mini-PCNL and RIRS for treating upper urinary calculi in various databases, and RevMan v.5.3 was applied. Three randomized controlled trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 37 publications
3
15
0
1
Order By: Relevance
“…The surgical outcomes of miniaturized PCNL are promising, with good SFRs, shorter hospital stay and reduced risk of morbidity, such as bleeding, adjacent organ injury and so on (LE:1) . Miniaturized PCNL and RIRS have similar indications for medium‐sized renal stones <3 cm; however, safety concerns regarding the higher bleeding risk, larger hemoglobin drop or longer hospital stay of miniaturized PCNL compared with RIRS arose (LE:1) …”
Section: Clinical Questions and Answersmentioning
confidence: 99%
See 1 more Smart Citation
“…The surgical outcomes of miniaturized PCNL are promising, with good SFRs, shorter hospital stay and reduced risk of morbidity, such as bleeding, adjacent organ injury and so on (LE:1) . Miniaturized PCNL and RIRS have similar indications for medium‐sized renal stones <3 cm; however, safety concerns regarding the higher bleeding risk, larger hemoglobin drop or longer hospital stay of miniaturized PCNL compared with RIRS arose (LE:1) …”
Section: Clinical Questions and Answersmentioning
confidence: 99%
“…186 Miniaturized PCNL and RIRS have similar indications for medium-sized renal stones <3 cm; 188 however, safety concerns regarding the higher bleeding risk, larger hemoglobin drop or longer hospital stay of miniaturized PCNL compared with RIRS arose (LE:1). 189,190 Bidirectional bilateral approach CQ 28. What is the algorithm for treatment of adult patients with symptomatic renal stones?…”
Section: Commentarymentioning
confidence: 99%
“…The stone-free rate is mainly correlated with the stone burden; however, most importantly, differences have been reported between different procedures [52]. The stone-free rate is the most important parameter to estimate the e cacy of all the approaches [53]. According to previous reports, PCNL and mPCNL have a higher stone-free rate than RIRS, although various imaging modalities were used.…”
Section: Discussionmentioning
confidence: 99%
“…Retrograde intrarenal surgery (RIRS) is another procedure for the treatment of upper urinary calculi. A high-quality meta-analysis showed that Miniperc provided signi cantly higher SFR compared with RIRS; however, Miniperc was accompanied with a higher incidence of postoperative complications [24].…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that the hospital stay time of Microperc is shorter, although not statistically signi cant. The possible reason is that Microperc has less damage and less postoperative discomfort [24]. Besides, it carries a lower urinary tract infection rate and hemoglobin drop.…”
Section: Discussionmentioning
confidence: 99%